Komposisi Gerak pada Pertunjukan Kesenian Tari Petuk di Desa Sade Kabupaten Lombok Tengah - Nur Aini Fajrianti; Yuspianal Imtihan (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2019)
This research aims to describe motion composition and presentation formation of Petuk dance at Sade Village Central Lombok.An approach used on this research is descriptif qualitative. The object is Petuk dance whichis cover motion composition and presentation formation. The technique for collecting all data by using 1) observation, 2) interview, and 3) documentation. The data is analyzed by 1) data reduction, 2) data presentation, and 3) Conclusion. While for checking data validity, this research used triangulation technique. This research shows some results, they are 1) motion composition include a) motion elements, b) kinds of motion, c) motion caracter. 2) presentation of petuk dance consist of a) petuk dance attribute, b) clothing, c) accompaniment, d) and property, e) decoration, f) lighting, g) place for presentation. From the results of the study it can be concluded that Petuk Dance is a dance art that requires many elements and types of movements. In Petuk Dance performances also require things like music, clothing, make-up. Keywords: Motion Composition, Presentation Formation, Petuk Dance.